Thermal insulation high-strength plastic floor and preparation method thereof
Patent Information
- Application Number
- CN202511698240.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-19
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2045-11-19
AI Technical Summary
[0002]塑料地板多以聚氯乙烯、聚丙烯、PETG(聚对苯二甲酸乙二醇酯-1,4-环己烷二甲醇酯)等为主要原料制备而成,但聚氯乙烯高温下易分解产生有毒气体,不利于环境和人体健康;单一聚丙烯属于易燃材料,遇火会迅速燃烧并产生熔滴,现有市场通常添加大量卤系或磷系阻燃剂来提升阻燃性,但会恶化加工性能与力学强度,并可能在生产与燃烧过程中释放有毒有害物质,与绿色环保的理念相悖
本发明提供一种隔热高强塑料地板及其制备方法,通过成分与工艺优化,将防护层、彩色层、功能层、防护层热压复合,得到强度高、阻燃性好、抗菌、隔热的多层复合塑料地板,大幅延长塑料地板的使用寿命与应用范围。
Smart Images

Figure IMAGE_BF83B5E2-3333-4E75-8975-B6B20E3F38FC
Abstract
Description
Technical Field
[0001] This invention relates to the field of plastic flooring technology, specifically to a heat-insulating high-strength plastic floor and its preparation method. Background Technology
[0002] Plastic flooring is mainly made of polyvinyl chloride (PVC), polypropylene, and PETG (polyethylene terephthalate-1,4-cyclohexanediol ester). However, PVC is prone to decomposition at high temperatures, producing toxic gases that are detrimental to the environment and human health. Polypropylene is a flammable material that burns rapidly and produces molten droplets when exposed to fire. The current market often adds a large amount of halogenated or phosphorus-based flame retardants to improve flame retardancy, but this deteriorates processing performance and mechanical strength, and may release toxic and harmful substances during production and combustion, which contradicts the concept of green environmental protection.
[0003] With the widespread use of underfloor heating systems, the insufficient thermal insulation performance of flooring can affect comfort. Although lightweight fillers such as hollow glass microspheres can be added to improve thermal insulation, their poor compatibility with the matrix often leads to a significant decrease in mechanical properties. At the same time, the industry usually uses inorganic antibacterial agents such as silver ions, zinc ions, or copper ions to improve the antibacterial properties of plastic flooring, but these agents are prone to migration and exudation during use, making it impossible to achieve long-lasting protection. Summary of the Invention
[0004] The purpose of this invention is to provide a heat-insulating high-strength plastic floor and its preparation method, so as to solve the problems in the prior art.
[0005] To solve the above-mentioned technical problems, the present invention provides the following technical solution: A method for preparing a heat-insulating high-strength plastic floor includes the following steps: S1: Polypropylene, PETG, composite porous calcium carbonate, epoxidized halloysite nanotubes, toughening agent, and compatibilizer are mixed, then extruded, granulated, and pressed into tablets to obtain a protective layer. S2: Polypropylene, PETG, colorant, toughening agent, compatibilizer and lubricant are mixed, then extruded, granulated and compressed into tablets to obtain a colored layer; S3: Polypropylene, PETG, aminated hollow glass microspheres, epoxidized halloysite nanotubes, toughening agent, compatibilizer, and lubricant are mixed, then extruded, granulated, and compressed into tablets to obtain the functional layer. S4: The protective layer, color layer, functional layer and protective layer are hot-pressed together to obtain a heat-insulating high-strength plastic floor.
[0006] Furthermore, the polypropylene is obtained by blending homopolymer polypropylene resin and copolymer polypropylene resin at a mass ratio of 2:3.
[0007] Furthermore, by weight, the raw material composition of the protective layer is: 100 parts polypropylene, 8-12 parts PETG, 2-6 parts composite porous calcium carbonate, 1-3 parts epoxidized halloysite nanotubes, 3-6 parts toughening agent, and 4-8 parts compatibilizer; the raw material composition of the colored layer is: 100 parts polypropylene, 8-12 parts PETG, 4-8 parts colorant, 4-9 parts toughening agent, 5-10 parts compatibilizer, and 3-6 parts lubricant.
[0008] Furthermore, by mass parts, the raw material composition of the functional layer is as follows: 100 parts polypropylene, 8-12 parts PETG, 3-9 parts aminated hollow glass microspheres, 1-3 parts epoxidized halloysite nanotubes, 5-10 parts toughening agent, 5-9 parts compatibilizer, and 4-8 parts lubricant.
[0009] Furthermore, the lubricant is one or more of stearic acid, polypropylene wax, and polyol ester; the compatibilizer is a polyolefin elastomer grafted with glycidyl methacrylate.
[0010] Furthermore, the preparation of the composite porous calcium carbonate includes the following steps: 1) Crush limestone, calcine it in air at 895-900℃ for 11-12 hours, cool it, ball mill it at 300-320 r / min for 50-60 minutes, and pass it through a 20-mesh sieve to obtain calcium oxide powder; mix the calcium oxide powder with ethylene glycol and stir for 1-2 hours, add oxalic acid solution, centrifuge at 8000 r / min, wash and dry it, and calcine it at 445-450℃ for 50-70 minutes to obtain ethylene glycol modified porous calcium carbonate; 2) Mix epoxy-branched polysiloxane quaternary ammonium salt and N,N-dimethylformamide, add ethylene glycol-modified porous calcium carbonate, sonicate for 10-20 min, add triethylamine, heat to 80-85℃, keep warm for 5-6 h, pour into anhydrous ethanol, centrifuge, wash, dry, and grind to obtain composite porous calcium carbonate.
[0011] Furthermore, the preparation of epoxidized halloysite nanotubes includes the following steps: Methanol and deionized water were mixed, γ-glycidoxypropyltrimethoxysilane was added, and the mixture was ultrasonically stirred for 10-20 min. Halloysite nanotubes were then added, and the mixture was stirred at 18-35℃ for 11-12 h. After centrifugation, washing, and drying, epoxidized halloysite nanotubes were obtained.
[0012] Furthermore, the mass ratio of composite porous calcium carbonate to halloysite nanotubes is 2:1.
[0013] Furthermore, the preparation of amination-modified hollow glass microspheres includes the following steps: A. Mix hollow glass microspheres with NaOH solution, sonicate for 20-30 min, filter, wash until neutral, and dry to obtain pretreated hollow glass microspheres; B. Mix hydrogen peroxide solution, ammonia solution, and deionized water, add pretreated hollow glass microspheres, heat to 90-95℃, stir for 30-40 minutes to obtain activated hollow glass microspheres; C. Mix anhydrous ethanol, deionized water, and 3-aminopropyltriethoxysilane, add activated hollow glass microspheres, heat to 65-70℃ and stir in a water bath for 2-3 hours, cool, filter, wash and dry to obtain aminated hollow glass microspheres.
[0014] Furthermore, the preparation of epoxy-branched polysiloxane quaternary ammonium salts includes the following steps: (1) Mix γ-glycidoxypropyltrimethoxysilane, phenyltrimethoxysilane and dodecyltrimethoxysilane, add acetic acid aqueous solution under stirring, heat to 58-60℃, add acetone and toluene, keep warm for 5-6h, and rotary evaporate to obtain epoxy-branched polysiloxane. (2) Mix hydrochloric acid and deionized water, and add triethylamine at 0-4℃ to obtain an aqueous solution of triethylamine hydrochloride; (3) Mix epoxy-branched polysiloxane and N,N-dimethylformamide, heat to add triethylamine hydrochloride aqueous solution, keep warm at 75-80℃ for 5-6h, reduce pressure, add toluene for azeotropic dehydration, distill under reduced pressure, and dry to obtain epoxy-branched polysiloxane quaternary ammonium salt.
[0015] Compared with the prior art, the beneficial effects of the present invention are: This invention provides a heat-insulating high-strength plastic floor and its preparation method. Through composition and process optimization, a protective layer, a colored layer, a functional layer, and a protective layer are hot-pressed together to obtain a multi-layer composite plastic floor with high strength, good flame retardancy, antibacterial properties, and heat insulation, which greatly extends the service life and application range of the plastic floor.
[0016] In this invention, polypropylene, which has low cost, good processing fluidity and chemical resistance, is selected as the multilayer base material. In order to improve the toughness of polypropylene, PETG, which has high toughness, impact resistance and excellent transparency, is introduced into the raw material. At the same time, additives are added to improve the compatibility between polypropylene and PETG. Calcium carbonate is commonly used as a filler in existing plastic products to improve rigidity, but it also faces problems such as easy agglomeration when added in large quantities and poor compatibility with the base material. In this invention, ethylene glycol-modified porous calcium carbonate is prepared using low-cost limestone as raw material and introduced into plastic flooring to effectively improve the material's toughness and heat insulation. To further improve the uniformity of dispersion of ethylene glycol-modified porous calcium carbonate in the base material, epoxy-branched polysiloxane quaternary ammonium salt is further grafted, which significantly improves the flame retardancy, water resistance, thermal stability, and antibacterial properties of the plastic flooring. The epoxy-branched polysiloxane quaternary ammonium salt is prepared by hydrolysis and condensation of phenyltrimethoxysilane, dodecyltrimethoxysilane, and γ-glycidyl etheroxypropyltrimethoxysilane to obtain branched polysiloxane containing phenyl, long-chain alkyl dodecyl, and epoxy groups. Then, it is prepared by ring-opening of the epoxy groups in the branched polysiloxane with triethylamine hydrochloride.
[0017] This invention introduces a composite porous calcium carbonate and epoxidized halloysite nanotubes as a filler in the protective layer. By controlling the feeding ratio, the epoxy groups in the epoxidized halloysite nanotubes interact with the composite porous calcium carbonate, and in synergy with a compatibilizer, a highly efficient flame-retardant and corrosion-resistant network is constructed to further improve the flame retardancy and corrosion resistance of the protective layer. Simultaneously, the prepared composite porous calcium carbonate has a certain lubricating effect, making it possible to prepare the protective layer without adding additional lubricants, thus simplifying the formulation. Aminated hollow glass microspheres and epoxidized halloysite nanotubes are combined as a functional layer filler to further improve the thermal insulation of the floor. This invention uses aminated hollow glass microspheres, epoxidized halloysite nanotubes, and composite porous calcium carbonate as raw materials. By controlling the feeding ratio, the thermal conductivity of the flooring is significantly reduced by utilizing the hollow structure and porous characteristics, improving the thermal insulation of the plastic flooring. At the same time, a multi-effect synergistic flame retardant system of gas phase barrier, solid phase toughening, and catalytic char formation is constructed, endowing the plastic flooring with green and environmentally friendly high flame retardancy. These modified particles are tightly bonded to the matrix, thereby significantly improving the mechanical strength and durability of the plastic flooring, thus extending its service life. Detailed Implementation
[0018] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0019] Furthermore, the technical solutions of the various embodiments can be combined with each other, but only if they are feasible for those skilled in the art. If the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such combination of technical solutions does not exist and is not within the scope of protection claimed by this invention.
[0020] The technical solution of the present invention will be further described in detail below with reference to specific embodiments. It should be understood that the following embodiments are only used to explain the present invention and are not intended to limit the present invention.
[0021] Example 1: A method for preparing a heat-insulating high-strength plastic floor, comprising the following steps: S1: Polypropylene, PETG, composite porous calcium carbonate, epoxidized halloysite nanotubes, toughening agent, and compatibilizer are mixed, then extruded, granulated, and pressed into tablets to obtain a protective layer. S2: Polypropylene, PETG, colorant, toughening agent, compatibilizer and lubricant are mixed, then extruded, granulated and compressed into tablets to obtain a colored layer; S3: Polypropylene, PETG, aminated hollow glass microspheres, epoxidized halloysite nanotubes, toughening agent, compatibilizer, and lubricant are mixed, then extruded, granulated, and compressed into tablets to obtain the functional layer. S4: The protective layer, colored layer, functional layer and protective layer are hot-pressed together to obtain a heat-insulating high-strength plastic flooring; The polypropylene is obtained by blending homopolymer polypropylene resin and copolymer polypropylene resin in a mass ratio of 2:3; the lubricant is stearic acid; and the compatibilizer is polyolefin elastomer grafted with glycidyl methacrylate. By weight, the raw material composition of the protective layer is: 100 parts polypropylene, 8 parts PETG, 2 parts composite porous calcium carbonate, 1 part epoxidized halloysite nanotubes, 3 parts toughening agent, and 4 parts compatibilizer; the raw material composition of the colored layer is: 100 parts polypropylene, 8 parts PETG, 4 parts colorant, 4 parts toughening agent, 5 parts compatibilizer, and 3 parts lubricant. The functional layer consists of the following raw materials by mass: 100 parts polypropylene, 8 parts PETG, 3 parts aminated hollow glass microspheres, 1 part epoxidized halloysite nanotubes, 5 parts toughening agent, 5 parts compatibilizer, and 4 parts lubricant. The preparation of the composite porous calcium carbonate includes the following steps: 1) Crush 10g of limestone, calcine it at 895℃ for 12h in air atmosphere, cool it, ball mill it, and pass it through a 20-mesh sieve to obtain calcium oxide powder; mix 0.5g of calcium oxide powder with 1L of 10% ethylene glycol and stir for 1h, add 1L of 10% oxalic acid solution, centrifuge at 8000r / min, wash and dry it, and calcine it at 450℃ for 60min to obtain ethylene glycol modified porous calcium carbonate; 2) Mix 6.4g of epoxy-branched polysiloxane quaternary ammonium salt and 50mL of N,N-dimethylformamide, add 1.2g of ethylene glycol-modified porous calcium carbonate, sonicate for 10min, add 0.1 equivalent of triethylamine, heat to 80℃, keep warm for 6h, pour into 500mL of anhydrous ethanol, centrifuge, wash, dry, and grind to obtain composite porous calcium carbonate; The preparation of epoxidized halloysite nanotubes includes the following steps: Mix 90 mL of methanol with 10 mL of deionized water, add 1 g of γ-glycidyl etheroxypropyltrimethoxysilane, sonicate for 10 min, add 5 g of halloysite nanotubes, stir at 18 °C for 12 h, centrifuge, wash, and dry to obtain epoxidized halloysite nanotubes. The preparation of amination-modified hollow glass microspheres includes the following steps: A. Mix 2g of hollow glass microspheres with 150mL of 3% NaOH solution, sonicate for 20min, filter, wash until neutral, and dry to obtain pretreated hollow glass microspheres; B. Mix 21.5 mL of hydrogen peroxide solution, 34.5 mL of ammonia solution, and 44 mL of deionized water, add the pretreated hollow glass microspheres, heat to 90 °C, and stir for 40 min to obtain activated hollow glass microspheres. C. Mix 72 mL of anhydrous ethanol, 8 mL of deionized water, and 2 mL of 3-aminopropyltriethoxysilane, add activated hollow glass microspheres, heat to 65 °C and stir in a water bath for 3 h, cool, filter, wash and dry to obtain aminated hollow glass microspheres. The preparation of epoxy-branched polysiloxane quaternary ammonium salts includes the following steps: (1) Mix 0.3 mol γ-glycidoxypropyltrimethoxysilane, 0.18 mol phenyltrimethoxysilane and 0.12 mol dodecyltrimethoxysilane, add 43.2 mL of acetic acid aqueous solution with pH 3 under stirring, heat to 58 °C, add 52.3 mL acetone and 83 mL toluene, keep warm for 5 h, and rotary evaporate to obtain epoxy-branched polysiloxane; (2) Under a nitrogen atmosphere, 2g of epoxy-branched polysiloxane and 25mL of anhydrous N,N-dimethylformamide were mixed, and 0.06g of triethylamine hydrochloride and 25mL of anhydrous N,N-dimethylformamide were added. The mixture was heated to 75℃ and kept at that temperature for 6h. After cooling, 200mL of anhydrous diethyl ether was added, and the mixture was filtered, washed, and dried to obtain epoxy-branched polysiloxane quaternary ammonium salt.
[0022] Example 2: A method for preparing a heat-insulating high-strength plastic floor, comprising the following steps: S1: Polypropylene, PETG, composite porous calcium carbonate, epoxidized halloysite nanotubes, toughening agent, and compatibilizer are mixed, then extruded, granulated, and pressed into tablets to obtain a protective layer. S2: Polypropylene, PETG, colorant, toughening agent, compatibilizer and lubricant are mixed, then extruded, granulated and compressed into tablets to obtain a colored layer; S3: Polypropylene, PETG, aminated hollow glass microspheres, epoxidized halloysite nanotubes, toughening agent, compatibilizer, and lubricant are mixed, then extruded, granulated, and compressed into tablets to obtain the functional layer. S4: The protective layer, colored layer, functional layer and protective layer are hot-pressed together to obtain a heat-insulating high-strength plastic flooring; The polypropylene is obtained by blending homopolymer polypropylene resin and copolymer polypropylene resin in a mass ratio of 2:3; the lubricant is stearic acid; and the compatibilizer is polyolefin elastomer grafted with glycidyl methacrylate. By weight, the raw material composition of the protective layer is: 100 parts polypropylene, 10 parts PETG, 4 parts composite porous calcium carbonate, 2 parts epoxidized halloysite nanotubes, 4 parts toughening agent, and 5 parts compatibilizer; the raw material composition of the colored layer is: 100 parts polypropylene, 10 parts PETG, 6 parts colorant, 7 parts toughening agent, 8 parts compatibilizer, and 4 parts lubricant. By mass, the raw material composition of the functional layer is as follows: 100 parts polypropylene, 10 parts PETG, 7 parts aminated hollow glass microspheres, 2 parts epoxidized halloysite nanotubes, 6 parts toughening agent, 7 parts compatibilizer, and 6 parts lubricant. The preparation of the composite porous calcium carbonate includes the following steps: 1) Crush 10g of limestone, calcine it at 898℃ for 11.5h in air atmosphere, cool it, ball mill it, and pass it through a 20-mesh sieve to obtain calcium oxide powder; mix 0.5g of calcium oxide powder with 1L of 10% ethylene glycol and stir for 1.5h, add 1L of 10% oxalic acid solution, centrifuge at 8000r / min, wash and dry it, and calcine it at 447℃ for 60min to obtain ethylene glycol modified porous calcium carbonate; 2) Mix 6.4g of epoxy-branched polysiloxane quaternary ammonium salt and 50mL of N,N-dimethylformamide, add 1.2g of ethylene glycol-modified porous calcium carbonate, sonicate for 15min, add 0.1 equivalent of triethylamine, heat to 83℃, keep warm for 5.5h, pour into 500mL of anhydrous ethanol, centrifuge, wash, dry, and grind to obtain composite porous calcium carbonate; The preparation of epoxidized halloysite nanotubes includes the following steps: Mix 90 mL of methanol with 10 mL of deionized water, add 1 g of γ-glycidyl etheroxypropyltrimethoxysilane, sonicate for 15 min, add 5 g of halloysite nanotubes, stir at 20 °C for 11.5 h, centrifuge, wash, and dry to obtain epoxidized halloysite nanotubes. The preparation of amination-modified hollow glass microspheres includes the following steps: A. Mix 2g of hollow glass microspheres with 150mL of 3% NaOH solution, sonicate for 25min, filter, wash until neutral, and dry to obtain pretreated hollow glass microspheres; B. Mix 21.5 mL of hydrogen peroxide solution, 34.5 mL of ammonia solution, and 44 mL of deionized water, add the pretreated hollow glass microspheres, heat to 93°C, and stir for 35 min to obtain activated hollow glass microspheres. C. Mix 72 mL of anhydrous ethanol, 8 mL of deionized water, and 2 mL of 3-aminopropyltriethoxysilane, add activated hollow glass microspheres, heat to 68 °C and stir in a water bath for 2.5 h, cool, filter, wash and dry to obtain aminated hollow glass microspheres. The preparation of epoxy-branched polysiloxane quaternary ammonium salts includes the following steps: (1) Mix 0.3 mol γ-glycidoxypropyltrimethoxysilane, 0.18 mol phenyltrimethoxysilane and 0.12 mol dodecyltrimethoxysilane, add 43.2 mL of acetic acid aqueous solution with pH 3 under stirring, heat to 59 °C, add 52.3 mL acetone and 83 mL toluene, keep warm for 5.5 h, and rotary evaporate to obtain epoxy-branched polysiloxane; (2) Under a nitrogen atmosphere, 2g of epoxy-branched polysiloxane and 25mL of anhydrous N,N-dimethylformamide were mixed, and 0.06g of triethylamine hydrochloride and 25mL of anhydrous N,N-dimethylformamide were added. The mixture was heated to 78℃ and kept at that temperature for 5.5h. After cooling, 200mL of anhydrous diethyl ether was added, filtered, washed, and dried to obtain epoxy-branched polysiloxane quaternary ammonium salt.
[0023] Example 3: A method for preparing a heat-insulating high-strength plastic floor, comprising the following steps: S1: Polypropylene, PETG, composite porous calcium carbonate, epoxidized halloysite nanotubes, toughening agent, and compatibilizer are mixed, then extruded, granulated, and pressed into tablets to obtain a protective layer. S2: Polypropylene, PETG, colorant, toughening agent, compatibilizer and lubricant are mixed, then extruded, granulated and compressed into tablets to obtain a colored layer; S3: Polypropylene, PETG, aminated hollow glass microspheres, epoxidized halloysite nanotubes, toughening agent, compatibilizer, and lubricant are mixed, then extruded, granulated, and compressed into tablets to obtain the functional layer. S4: The protective layer, colored layer, functional layer and protective layer are hot-pressed together to obtain a heat-insulating high-strength plastic flooring; The polypropylene is obtained by blending homopolymer polypropylene resin and copolymer polypropylene resin in a mass ratio of 2:3; the lubricant is stearic acid; and the compatibilizer is polyolefin elastomer grafted with glycidyl methacrylate. By weight, the raw material composition of the protective layer is: 100 parts polypropylene, 12 parts PETG, 6 parts composite porous calcium carbonate, 3 parts epoxidized halloysite nanotubes, 6 parts toughening agent, and 8 parts compatibilizer; the raw material composition of the colored layer is: 100 parts polypropylene, 12 parts PETG, 8 parts colorant, 9 parts toughening agent, 10 parts compatibilizer, and 6 parts lubricant. The functional layer is composed of the following raw materials by mass: 100 parts polypropylene, 12 parts PETG, 9 parts aminated hollow glass microspheres, 3 parts epoxidized halloysite nanotubes, 10 parts toughening agent, 9 parts compatibilizer, and 8 parts lubricant. The preparation of the composite porous calcium carbonate includes the following steps: 1) Crush 10g of limestone, calcine it at 900℃ for 11h in air atmosphere, cool it, ball mill it, and pass it through a 20-mesh sieve to obtain calcium oxide powder; mix 0.5g of calcium oxide powder with 1L of 10% ethylene glycol and stir for 2h, add 1L of 10% oxalic acid solution, centrifuge at 8000r / min, wash and dry it, and calcine it at 450℃ for 50min to obtain ethylene glycol modified porous calcium carbonate; 2) Mix 6.4g of epoxy-branched polysiloxane quaternary ammonium salt and 50mL of N,N-dimethylformamide, add 1.2g of ethylene glycol-modified porous calcium carbonate, sonicate for 20min, add 0.1 equivalent of triethylamine, heat to 85℃, keep warm for 5h, pour into 500mL of anhydrous ethanol, centrifuge, wash, dry, and grind to obtain composite porous calcium carbonate; The preparation of epoxidized halloysite nanotubes includes the following steps: Mix 90 mL of methanol with 10 mL of deionized water, add 1 g of γ-glycidyl etheroxypropyltrimethoxysilane, sonicate for 20 min, add 5 g of halloysite nanotubes, stir at 35 °C for 11 h, centrifuge, wash, and dry to obtain epoxidized halloysite nanotubes. The preparation of amination-modified hollow glass microspheres includes the following steps: A. Mix 2g of hollow glass microspheres with 150mL of 3% NaOH solution, sonicate for 30min, filter, wash until neutral, and dry to obtain pretreated hollow glass microspheres; B. Mix 21.5 mL of hydrogen peroxide solution, 34.5 mL of ammonia solution, and 44 mL of deionized water, add the pretreated hollow glass microspheres, heat to 95 °C, and stir for 30 min to obtain activated hollow glass microspheres. C. Mix 72 mL of anhydrous ethanol, 8 mL of deionized water, and 2 mL of 3-aminopropyltriethoxysilane, add activated hollow glass microspheres, heat to 70 °C and stir in a water bath for 2 h, cool, filter, wash and dry to obtain aminated hollow glass microspheres. The preparation of epoxy-branched polysiloxane quaternary ammonium salts includes the following steps: (1) Mix 0.3 mol γ-glycidoxypropyltrimethoxysilane, 0.18 mol phenyltrimethoxysilane and 0.12 mol dodecyltrimethoxysilane, add 43.2 mL of acetic acid aqueous solution with pH 3 under stirring, heat to 60 °C, add 52.3 mL acetone and 83 mL toluene, keep warm for 6 h, and rotary evaporate to obtain epoxy-branched polysiloxane; (2) Under a nitrogen atmosphere, 2g of epoxy-branched polysiloxane and 25mL of anhydrous N,N-dimethylformamide were mixed, and 0.06g of triethylamine hydrochloride and 25mL of anhydrous N,N-dimethylformamide were added. The mixture was heated to 80℃ and kept at that temperature for 5h. After cooling, 200mL of anhydrous diethyl ether was added, and the mixture was filtered, washed, and dried to obtain epoxy-branched polysiloxane quaternary ammonium salt.
[0024] Comparative Example 1: Using Example 3 as the control group, ethylene glycol-modified porous calcium carbonate was used to replace the composite porous calcium carbonate, while other processes were normal.
[0025] Comparative Example 2: Using Example 3 as the control group, the mass ratio of composite porous calcium carbonate and epoxidized halloysite nanotubes was 1:1, that is, 3 parts of composite porous calcium carbonate, and other processes were normal.
[0026] In the examples and comparative examples, the thickness of the protective layer and the pigment layer is 0.5 mm, and the thickness of the functional layer is 2 mm.
[0027] Sources of raw materials used (for illustrative purposes only): PETGCR-5083: China Resources Chemical; Polyolefin elastomer grafted glycidyl methacrylate 5541254: Dongguan Shenghao Plastic Raw Materials Co., Ltd.; Halloysite nanotubes H431905: Aladdin reagent; Hollow glass microspheres K1: 3M; Pigment (Pigment Blue 15, 99%), Homopolymer polypropylene resin (injection molding grade, melt flow rate 27g / 10min), Copolymer polypropylene resin (injection molding grade, block copolymer polypropylene, melt flow rate 21g / 10min), Stearic acid (99%), γ-glycidyl etheroxypropyltrimethoxysilane (97%), Phenyltrimethoxysilane (98%), Dodecyltrimethoxysilane (99%), Triethylamine hydrochloride (99%), commercially available.
[0028] Performance testing: The plastic flooring prepared in the examples and comparative examples was tested. Thermal conductivity: tested using a thermal conductivity meter; Impact resistance: 50mm long and 120mm wide, characterized by notched impact strength, tested according to GB / T 1843; Flame retardancy: UL-94 vertical flammability test; Antibacterial durability: the floor was rinsed 100 times with 30℃ deionized water, dried, and the antibacterial rate was measured using Escherichia coli as the test species, employing the plate method; the results are shown in Table 1. Table 1 This invention provides a heat-insulating high-strength plastic floor and its preparation method. Through composition and process optimization, a protective layer, a colored layer, a functional layer, and a protective layer are hot-pressed together to obtain a multi-layer composite plastic floor with high strength, good flame retardancy, antibacterial properties, and heat insulation. This significantly extends the service life and application range of the plastic floor. In Table 1, / indicates that it was not tested.
[0029] Comparing Example 3 with Comparative Example 1, it can be seen that calcium carbonate is often used as a filler in existing plastic products to improve rigidity. However, it also faces problems such as easy agglomeration when added in large quantities and poor compatibility with the base material. In this invention, ethylene glycol modified porous calcium carbonate is prepared using low-cost limestone as raw material and introduced into plastic flooring to effectively improve the toughness and heat insulation of the material. In order to further improve the uniformity of dispersion of ethylene glycol modified porous calcium carbonate in the base material, epoxy-branched polysiloxane quaternary ammonium salt is further grafted, which significantly improves the flame retardancy, water resistance, thermal stability and antibacterial properties of plastic flooring. The epoxy-branched polysiloxane quaternary ammonium salt is prepared by hydrolysis and condensation of phenyltrimethoxysilane, dodecyltrimethoxysilane and γ-glycidyl etheroxypropyltrimethoxysilane to obtain branched polysiloxane containing phenyl, long-chain alkyl dodecyl and epoxy groups. Then, it is prepared by ring-opening of the epoxy groups in the branched polysiloxane with triethylamine hydrochloride.
[0030] Comparing Example 3 with Comparative Example 2, it can be seen that the present invention introduces a composite porous calcium carbonate and epoxidized halloysite nanotubes as a filler in the protective layer. By controlling the feeding ratio, the epoxy groups in the epoxidized halloysite nanotubes interact with the composite porous calcium carbonate, and work synergistically with the compatibilizer to construct a highly efficient flame-retardant and corrosion-resistant network, thereby further improving the flame retardancy and corrosion resistance of the protective layer. At the same time, the prepared composite porous calcium carbonate has a certain lubricating effect, making it possible to prepare the protective layer without adding additional lubricant, thus simplifying the formulation.
[0031] The above description is merely an embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural transformations made using the present invention's specification under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included within the patent protection scope of the present invention.
Claims
1. A method for preparing a heat-insulating high-strength plastic floor, characterized in that, Includes the following steps: S1: Polypropylene, PETG, composite porous calcium carbonate, epoxidized halloysite nanotubes, toughening agent, and compatibilizer are mixed, then extruded, granulated, and pressed into tablets to obtain a protective layer. S2: Polypropylene, PETG, colorant, toughening agent, compatibilizer, and lubricant are mixed, then extruded, granulated, and compressed into tablets to obtain a colored layer; S3: Polypropylene, PETG, aminated hollow glass microspheres, epoxidized halloysite nanotubes, toughening agent, compatibilizer, and lubricant are mixed, then extruded, granulated, and compressed into tablets to obtain the functional layer. S4: The protective layer, colored layer, functional layer and protective layer are hot-pressed together to obtain a heat-insulating high-strength plastic flooring; The preparation of the composite porous calcium carbonate includes the following steps: 1) Crush limestone, calcine it in air at 895-900℃ for 11-12 hours, cool it, ball mill it, and sieve it to obtain calcium oxide powder; mix the calcium oxide powder with ethylene glycol and stir for 1-2 hours, add oxalic acid solution, centrifuge, wash and dry it, and calcine it at 445-450℃ for 50-70 minutes to obtain ethylene glycol modified porous calcium carbonate; 2) Mix epoxy-branched polysiloxane quaternary ammonium salt and N,N-dimethylformamide, add ethylene glycol-modified porous calcium carbonate, sonicate for 10-20 min, add triethylamine, heat to 80-85℃, keep warm for 5-6 h, pour into anhydrous ethanol, centrifuge, wash, dry, and grind to obtain composite porous calcium carbonate. The preparation of epoxy-branched polysiloxane quaternary ammonium salts includes the following steps: (1) Mix γ-glycidoxypropyltrimethoxysilane, phenyltrimethoxysilane and dodecyltrimethoxysilane, add acetic acid aqueous solution under stirring, heat to 58-60℃, add acetone and toluene, keep warm for 5-6h, and rotary evaporate to obtain epoxy-branched polysiloxane. (2) Under a nitrogen atmosphere, epoxy-branched polysiloxane and anhydrous N,N-dimethylformamide are mixed, and a mixture of triethylamine hydrochloride and anhydrous N,N-dimethylformamide is added. The mixture is heated to 75-80℃ and kept at that temperature for 5-6 hours. After cooling, anhydrous diethyl ether is added, and the mixture is filtered, washed, and dried to obtain epoxy-branched polysiloxane quaternary ammonium salt.
2. The method for preparing a heat-insulating high-strength plastic floor according to claim 1, characterized in that, The polypropylene is obtained by blending homopolymer polypropylene resin and copolymer polypropylene resin at a mass ratio of 2:
3.
3. The method for preparing a heat-insulating high-strength plastic floor according to claim 1, characterized in that, The lubricant is one or more of stearic acid, polypropylene wax, and polyol ester; the compatibilizer is polyolefin elastomer grafted with glycidyl methacrylate.
4. The method for preparing a heat-insulating high-strength plastic floor according to claim 1, characterized in that, The mass ratio of composite porous calcium carbonate to epoxidized halloysite nanotubes in the protective layer is 2:
1.
5. The method for preparing a heat-insulating high-strength plastic floor according to claim 1, characterized in that, By weight, the raw material composition of the protective layer is: 100 parts polypropylene, 8-12 parts PETG, 2-6 parts composite porous calcium carbonate, 1-3 parts epoxidized halloysite nanotubes, 3-6 parts toughening agent, and 4-8 parts compatibilizer; the raw material composition of the colored layer is: 100 parts polypropylene, 8-12 parts PETG, 4-8 parts colorant, 4-9 parts toughening agent, 5-10 parts compatibilizer, and 3-6 parts lubricant.
6. The method for preparing a heat-insulating high-strength plastic floor according to claim 1, characterized in that, By mass, the raw material composition of the functional layer is as follows: 100 parts polypropylene, 8-12 parts PETG, 3-9 parts aminated hollow glass microspheres, 1-3 parts epoxidized halloysite nanotubes, 5-10 parts toughening agent, 5-9 parts compatibilizer, and 4-8 parts lubricant.
7. The method for preparing a heat-insulating high-strength plastic floor according to claim 1, characterized in that, The preparation of epoxidized halloysite nanotubes includes the following steps: Methanol and deionized water were mixed, γ-glycidoxypropyltrimethoxysilane was added, and the mixture was ultrasonically stirred for 10-20 min. Halloysite nanotubes were then added, and the mixture was stirred at 18-35℃ for 11-12 h. After centrifugation, washing, and drying, epoxidized halloysite nanotubes were obtained.
8. A heat-insulating, high-strength plastic flooring, characterized in that, It is prepared by the preparation method described in any one of claims 1-7.
Citation Information
Patent Citations
Decoration process of ancient building and pseudo-classic architecture
CN111706021A
Composite floor and preparation method therefor
WO2017016206A1